Isolation film, method for manufacturing the same, and secondary battery and power using device related thereto

CN116964852BActive Publication Date: 2026-10-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380010373.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2026-10-27
Estimated Expiration
2043-02-21

AI Technical Summary

Benefits of technology

[0070]本申请的用电装置包括本申请提供的二次电池,因而至少具有与所述二次电池相同的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116964852B_ABST
    Figure CN116964852B_ABST
Patent Text Reader

Abstract

The present application provides an isolation film, a preparation method thereof, and a secondary battery and a power device related thereto, the isolation film including a porous substrate and a coating layer disposed on at least one surface of the porous substrate, the coating layer including a three-dimensional skeleton structure and silicone particles, at least a portion of the silicone particles being filled in the three-dimensional skeleton structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a separator, its preparation method, and related secondary batteries and electrical devices. Background Technology

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. With the increasing application and promotion of secondary batteries, the requirements for their reliability have become increasingly stringent. How to continuously improve the reliability of secondary batteries without affecting their other performance characteristics remains a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0003] This application provides a separator, its preparation method, and related secondary batteries and power devices, which enable secondary batteries to achieve high energy density, high thermal stability, long cycle life, and good kinetic performance.

[0004] A first aspect of this application provides an isolation membrane comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein the coating comprises a three-dimensional skeleton structure and organosilicon particles, at least a portion of the organosilicon particles filling the three-dimensional skeleton structure.

[0005] By forming a coating comprising a three-dimensional framework structure and organosilicon particles on the surface of a porous substrate for a separator, and by filling at least a portion of the organosilicon particles into the three-dimensional framework structure, the separator can achieve high heat resistance, high adhesion, and high ion conductivity. Consequently, the secondary battery can also achieve high energy density, high thermal stability, long cycle life, and good kinetic performance.

[0006] In any embodiment of this application, the volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, in nm; the average diameter of the material constituting the three-dimensional framework structure is denoted as D1, in nm; and the average length of the material constituting the three-dimensional framework structure is denoted as L1, in nm. and

[0007] By adjusting and Within the aforementioned range, it is beneficial for the silicone particles and the three-dimensional skeleton structure to overlap and form an integrated effect, giving the coating a more stable spatial network structure. This can further improve the heat resistance, adhesion and ion conductivity of the separator, and also further improve the thermal stability, cycle performance and kinetic performance of the secondary battery.

[0008] In any embodiment of this application, Optionally,

[0009] In any embodiment of this application, Optionally,

[0010] This can better improve the heat resistance, adhesion and ion conductivity of the separator, and also better improve the thermal stability, cycle performance and kinetic performance of the secondary battery.

[0011] In any embodiment of this application, the volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, where d1 is less than or equal to 2000 nm and can be selected as 275-1500 nm. A smaller volume distribution particle size Dv50 of the organosilicon particles is beneficial for filling in the three-dimensional framework structure, forming a nested effect, and increasing the heat resistance, adhesion, and ion conductivity of the separator.

[0012] In any embodiment of this application, the average diameter of the material constituting the three-dimensional skeleton structure is denoted as D1, where D1 is less than or equal to 50 nm and can be selected as 10-42 nm. When the average diameter of the material constituting the three-dimensional skeleton structure is within the above range, the ion conductivity and voltage breakdown resistance of the separator can be further improved, and it also helps to form an integrated effect with the organosilicon particles, thereby further improving the heat resistance of the separator.

[0013] In any embodiment of this application, the average length of the material constituting the three-dimensional framework structure is denoted as L1, where L1 is 100-3500 nm, and optionally 400-3000 nm. When the average length of the material constituting the three-dimensional framework structure is within the above range, the heat resistance and ion conductivity of the separator can be further improved.

[0014] In any embodiment of this application, the morphology of the organosilicon particles includes spherical and / or near-spherical shapes.

[0015] In any embodiment of this application, the volume distribution particle size Dv90 of the organosilicon particles is less than or equal to 3500 nm, and can be selected as 800-2500 nm. A smaller volume distribution particle size Dv90 of the organosilicon particles is beneficial for forming a uniform coating.

[0016] In any embodiment of this application, the specific surface area of ​​the organosilicon particles is denoted as S, and its unit is m². 2 / g, 5.0m 2 / g≤S≤12.0m 2 / g, optionally, 6.0m 2 / g≤S≤10.0m 2 / g. When the specific surface area of ​​organosilicon particles is within the above range, it is beneficial for good overlap between particles, making it easier for organosilicon particles to form a porous structure, which is conducive to the migration of active ions.

[0017] In any embodiment of this application, the true density of the organosilicon particles is 1.0-2.0 g / cm³. 3 The concentration can be selected as 1.2-1.7 g / cm³. 3 When the true density of the silicone particles is within the above range, the compaction density and bulk density of the material increase, which helps to improve the heat resistance of the separator and also helps to reduce coating defects.

[0018] In any embodiment of this application, the compacted density of the organosilicon particles at 30000N is 0.3-1.5 g / cm³. 3 The concentration can be selected as 0.5-1.0 g / cm³. 3 .

[0019] When the compaction density of organosilicon particles is within the above range, the compaction density and bulk density of the material increase, which helps to improve the heat resistance of the separator and also helps to reduce coating defects.

[0020] In any embodiment of this application, the number average molecular weight of the organosilicon particles is between 20,000 and 80,000, optionally between 30,000 and 50,000. When the number average molecular weight of the organosilicon particles is within the above range, it is beneficial to form organosilicon particles with smaller particle sizes, enabling thinner coatings, reducing the overall thickness of the separator, and thus facilitating the improvement of the energy density of the secondary battery.

[0021] In any embodiment of this application, the content of the silicone particles is greater than or equal to 50 wt%, optionally 50-90 wt%, based on the total weight of the coating. When the content of silicone particles is within the above range, the overall adhesion, stability, swelling resistance, and heat resistance of the separator can be further improved.

[0022] In any embodiment of this application, the content of the three-dimensional skeleton structure is less than 50 wt%, and can be selected as 8-48 wt%, based on the total weight of the coating.

[0023] In any embodiment of this application, the organosilicon particles include a first structural unit;

[0024] The first structural unit is shown in equation (I):

[0025]

[0026] In equation (I), R 20 To R 27Each independently comprises one or more of substituted or unsubstituted C1-C10 alkyl groups, structural units as shown in formula (I-1), R 20 To R 27 At least one of them includes the structural unit shown in equation (I-1),

[0027]

[0028] In equation (I-1), R 28 Includes one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R 28 Including hydrogen atoms, or substituted or unsubstituted C1-C3 alkyl groups; R 29 Includes substituted or unsubstituted C1-C10 alkyl groups; optionally, R 29 Including substituted or unsubstituted C3-C10 alkyl groups.

[0029] In any embodiment of this application, the organosilicon particles further include a second structural unit and / or a third structural unit.

[0030] The second structural unit has the structure shown in equation (II):

[0031]

[0032] In formula (II), R1 includes one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R1 includes one or more of hydrogen atoms, substituted or unsubstituted C1-C3 alkyl groups; R2 includes one or more of substituted or unsubstituted C1-C20 alkyl groups, substituted or unsubstituted C3-C20 cycloalkyl groups, and substituted or unsubstituted C1-C20 hydroxyalkyl groups; optionally, R2 includes one or more of C1-C12 alkyl groups, C3-C12 cycloalkyl groups, and C1-C12 hydroxyalkyl groups.

[0033] The third structural unit is shown in equation (III):

[0034]

[0035] In formula (III), R3 includes one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R3 includes one or more of hydrogen atoms, substituted or unsubstituted C1-C3 alkyl groups.

[0036] In any embodiment of the present application, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is denoted as A%, 0 < A ≤ 20; optionally, 5 ≤ A ≤ 20. When the molar content of the first structural unit is within the above range, the heat resistance of the silicone particles can be improved, and its proportion is relatively small, which is beneficial to increasing the proportions of the second structural unit and the third structural unit, and improving the overall properties of the silicone particles such as cohesiveness, stability and swelling resistance.

[0037] In any embodiment of the present application, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the second structural unit is denoted as B%, 60 ≤ B < 100; optionally, 60 ≤ B ≤ 80. When the molar content of the second structural unit is within the above range, its proportion in the silicone particles is relatively large, which can improve the flexibility of the silicone particles, so that the cohesiveness of the silicone particles is significantly improved; when the silicone particles are applied to a separator, the bonding force between the silicone particles and the substrate of the separator can be enhanced.

[0038] In any embodiment of the present application, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the third structural unit is denoted as C%, 0 < C ≤ 20; optionally, 5 ≤ C ≤ 20. When the molar content of the third structural unit is within the above range, the stability of the silicone particles can be significantly improved.

[0039] In any embodiment of the present application, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is denoted as A%, the molar content of the second structural unit is denoted as B%, the molar content of the third structural unit is denoted as C%, and the silicone particles satisfy at least one of the following conditions (1) to (3): (1) 3 ≤ B / C ≤ 16; (2) 3 ≤ B / A ≤ 16; (3) B:C:A is (12 to 16):(1 to 4):(1 to 4).

[0040] When the molar contents of the first structural unit, the second structural unit and the third structural unit satisfy the above ratios, the three structural units in the silicone particles cooperate with each other to jointly improve the cohesiveness, stability, swelling resistance and thermal stability of the silicone particles.

[0041] In any embodiment of the present application, the silicone particles include the structural unit represented by formula (a):

[0042]

[0043] In formula (a), R 14 and R 15Each is independently selected from hydrogen atoms, substituted or unsubstituted C1-C10 alkyl, hydroxyl, or amino groups; optionally, R 14 and R 15 Each is independently selected from hydrogen atoms, substituted or unsubstituted C1-C6 alkyl, hydroxyl or amino atoms.

[0044] Optionally, the organosilicon particles include one or more of polymethylsiloxane, polydimethylsiloxane, polydiethylsiloxane, polymethylhydroxysiloxane, polymethylaminosiloxane, and their respective derivatives.

[0045] In any embodiment of this application, the material constituting the three-dimensional skeleton structure includes at least one of wires, rods, tubes, and poles.

[0046] In any embodiment of this application, the aspect ratio of the material constituting the three-dimensional skeleton structure is from 5 to 150, and optionally from 20 to 100. When the aspect ratio of the material constituting the three-dimensional skeleton structure is within the above range, the ion conductivity of the separator and its wetting and retention properties with the electrolyte can be further improved.

[0047] In any embodiment of this application, the material constituting the three-dimensional skeleton structure includes at least one of organic and inorganic materials.

[0048] In any embodiment of this application, the organic material includes at least one of cellulose nanofibers, polytetrafluoroethylene nanofibers, and polyamide nanofibers. Optionally, the cellulose nanofibers include at least one of cellulose nanofibers, cellulose nanowhiskers, and bacterial cellulose nanofibers.

[0049] In any embodiment of this application, the inorganic material includes at least one of halloysite nanotubes, nanorod-shaped alumina, nanorod-shaped boehmite, nanorod-shaped silica, and glass fiber.

[0050] In any embodiment of this application, the material constituting the three-dimensional framework structure includes nanocellulose, which includes at least one of unmodified nanocellulose and modified nanocellulose.

[0051] In any embodiment of this application, the modified nanocellulose includes a modifying group, which includes at least one of amino, carboxyl, aldehyde, sulfonic acid, boric acid and phosphate groups, and optionally includes at least one of sulfonic acid, boric acid and phosphate groups.

[0052] In any embodiment of this application, the modified nanocellulose includes hydroxyl groups and modified groups, and the molar ratio of the modified groups to the hydroxyl groups is 1:4 to 4:1, optionally 2:3 to 7:3. When the molar ratio of the modified groups to the hydroxyl groups is within the above range, the heat resistance, ion conductivity, and wetting and retention properties of the separator can be further improved.

[0053] In any embodiment of this application, the material constituting the three-dimensional skeleton structure includes sulfonic acid groups, and the sulfur content in the material constituting the three-dimensional skeleton structure is ≥0.1wt%, optionally 0.2-0.5wt%, based on the total weight of the material constituting the three-dimensional skeleton structure.

[0054] In any embodiment of this application, the coating further includes a non-particulate binder.

[0055] In any embodiment of this application, the content of the non-particulate binder in the coating is ≤5 wt%, based on the total weight of the coating.

[0056] In any embodiment of this application, the non-particulate binder includes at least one of polyacrylonitrile, acrylic resin, acrylate resin, polyvinyl alcohol, isobutylene-maleic anhydride copolymer, polyacrylamide, sodium carboxymethyl cellulose, carboxymethyl chitosan, sodium alginate, and derivatives thereof.

[0057] In any embodiment of this application, the thickness of the porous substrate is ≤6μm, and can be 3-5μm.

[0058] In any embodiment of this application, the thickness of the coating is ≤4μm, and can be selected as 0.4-3μm.

[0059] In any embodiment of this application, the longitudinal thermal shrinkage rate of the separator at 150°C for 1 hour is ≤4.5%, and can be selected as 0.8%-3%.

[0060] In any embodiment of this application, the lateral thermal shrinkage rate of the separator at 150°C for 1 hour is ≤4.5%, and can be selected as 1%-3%.

[0061] In any embodiment of this application, the longitudinal tensile strength of the separator is ≥1600 kg / cm². 2 Available in 1800-4500 kg / cm² 2 .

[0062] In any embodiment of this application, the transverse tensile strength of the separator is ≥1600 kg / cm². 2 Available in 1800-4500 kg / cm² 2 .

[0063] In any embodiment of this application, the wetting length of the separator is ≥20mm, and can be 30-80mm.

[0064] In any embodiment of this application, the wetting speed of the separator is ≥2 mm / s, and can be selected as 3-10 mm / s.

[0065] In any embodiment of this application, the air permeability of the isolation membrane is ≤350s / 100mL, and can be selected as 100-270s / 100mL.

[0066] In any embodiment of this application, the ion conductivity of the separator is ≥0.5mS / cm, and can be selected as 0.55-0.98mS / cm.

[0067] The second aspect of this application provides a method for preparing the isolation membrane of the first aspect of this application, comprising the following steps: providing a porous substrate; kneading organosilicon particles with a binder, adding a material for forming a three-dimensional skeleton structure and a solvent, mixing uniformly to prepare a coating slurry; coating the coating slurry onto at least one surface of the porous substrate, and drying to obtain an isolation membrane, wherein the isolation membrane comprises a porous substrate and a coating disposed on at least one surface of the porous substrate, the coating comprising a three-dimensional skeleton structure and organosilicon particles, at least a portion of the organosilicon particles filling the three-dimensional skeleton structure.

[0068] A third aspect of this application provides a secondary battery, including the separator of the first aspect of this application or the separator prepared by the method of the second aspect of this application.

[0069] The fourth aspect of this application provides an electrical device, including the secondary battery of the third aspect of this application.

[0070] The electrical device of this application includes the secondary battery provided in this application, and therefore has at least the same advantages as the secondary battery. Attached Figure Description

[0071] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0072] Figure 1 This is a schematic diagram of one embodiment of the secondary battery of this application.

[0073] Figure 2 yes Figure 1An exploded view of the implementation method of the secondary battery.

[0074] Figure 3 This is a schematic diagram of one embodiment of the battery module of this application.

[0075] Figure 4 This is a schematic diagram of one embodiment of the battery pack of this application.

[0076] Figure 5 yes Figure 4 An exploded view of an embodiment of the battery pack shown.

[0077] Figure 6 This is a schematic diagram of one embodiment of an electrical device that uses a secondary battery as a power source, as described in this application.

[0078] The accompanying drawings are not necessarily drawn to scale. The reference numerals are as follows: 1 Battery pack, 2 Upper casing, 3 Lower casing, 4 Battery module, 5 Secondary battery, 51 Housing, 52 Electrode assembly, 53 Cover plate. Detailed Implementation

[0079] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the separator, its preparation method, and related secondary batteries and power-consuming devices of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0080] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0081] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0082] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0083] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0084] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0085] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0086] Unless otherwise specified, in this application, the terms "first," "second," "third," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0087] In this application, the terms "multiple", "various", etc., refer to two or more kinds.

[0088] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0089] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application. Unless otherwise stated, the test temperature is 25°C.

[0090] The term "alkyl" encompasses both straight-chain and branched alkyl groups. For example, alkyl groups can be C1 to C50 alkyl, C1 to C40 alkyl, C1 to C30 alkyl, C1 to C20 alkyl, C1 to C12 alkyl, C1 to C10 alkyl, C1 to C6 alkyl, C1 to C5 alkyl, and C1 to C3 alkyl. In some embodiments, alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, etc. Additionally, alkyl groups may optionally be substituted.

[0091] The term "cycloalkyl" refers to a cyclic structure consisting of three or more carbon atoms. For example, cycloalkyl groups can be C3 to C50, C3 to C40, C3 to C30, C3 to C20, C3 to C12, C3 to C10, C3 to C6, or C3 to C4. In some embodiments, cycloalkyl groups include cyclopropyl, cycloisopropyl, cyclobutyl, cycloisobutyl, cyclotert-butyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, etc. Additionally, cycloalkyl groups may optionally be substituted.

[0092] The term "hydroxyalkyl" refers to an alkyl group in which one hydrogen atom is replaced by a hydroxyl group. For example, hydroxyalkyl can be C1 to C50 hydroxyalkyl, C1 to C40 hydroxyalkyl, C1 to C30 hydroxyalkyl, C1 to C20 hydroxyalkyl, C1 to C12 hydroxyalkyl, C1 to C10 hydroxyalkyl, C1 to C6 hydroxyalkyl, C1 to C5 hydroxyalkyl, or C1 to C3 hydroxyalkyl. In some embodiments, the alkyl group includes hydroxymethyl, hydroxyethyl, hydroxypropyl, hydroxyisopropyl, hydroxybutyl, hydroxyisobutyl, hydroxytert-butyl, hydroxypentyl, hydroxyhexyl, hydroxyheptyl, hydroxyoctyl, etc. Additionally, the alkyl group may optionally be substituted.

[0093] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).

[0094] Throughout this specification, substituents of compounds are disclosed by groups or ranges. It is expressly intended that such description include each individual sub-combination of members of these groups and ranges. For example, it is expressly intended that the term "C1 to C8 alkyl" individually discloses C1, C2, C3, C4, C5, C6, C7, C8, C1 to C8, C1 to C7, C1 to C6, C1 to C5, C1 to C4, C1 to C3, C1 to C2, C2 to C8, C2 to C7, C2 to C6, C2 to C5, C2 to C4, C2 to C3, C3 to C8, C3 to C7, C3 to C6, C3 to C5, C3 to C4, C4 to C8, C4 to C7, C4 to C6, C4 to C5, C5 to C8, C5 to C7, C5 to C6, C6 to C8, C6 to C7, and C7 to C8 alkyl. As other examples, it is explicitly anticipated that integers ranging from 5 to 40 will be disclosed individually as 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, and 40; and it is explicitly anticipated that integers ranging from 1 to 20 will be disclosed individually as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. Based on this, other groups or ranges can be explicitly anticipated.

[0095] When the above groups (e.g., alkyl, cycloalkyl, hydroxyalkyl, etc.) are described as substituted, the substituted groups may include halogen atoms or heteroatoms.

[0096] The term "halogen atom" includes fluorine atoms, chlorine atoms, bromine atoms, etc.

[0097] The term "heteroatoms" includes nitrogen atoms, sulfur atoms, phosphorus atoms, etc.

[0098] Typically, a secondary battery consists of an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator. The separator is placed between the positive and negative electrodes and mainly serves to prevent short circuits between the positive and negative electrodes, while also allowing active ions to pass freely to form a circuit.

[0099] With the increasing application and promotion of rechargeable batteries, people have higher and higher requirements for their performance (such as reliability). The separator is a crucial component of rechargeable batteries, and improving its performance can enhance their reliability. Currently, commercially available rechargeable batteries typically use polyolefin porous membranes as separators, which have poor heat resistance and exhibit significant thermal shrinkage when heated. This can cause direct contact between the positive and negative electrodes inside the battery, leading to internal short circuits and increasing the safety risks of the rechargeable battery.

[0100] To address these issues, current methods primarily involve coating a heat-resistant inorganic ceramic layer onto a polyolefin porous membrane. However, the improvement in the heat resistance of the separator by the inorganic ceramic layer is limited; furthermore, the inorganic ceramic layer exhibits poor adhesion, leading to powder shedding, and its adhesion to both the positive and negative electrode sheets is also poor. Coating the polyolefin porous membrane with a polymer-containing coating can improve the coating's adhesion; however, polymer coatings still suffer from high-temperature shrinkage, and their ion conductivity is also poor.

[0101] It is evident that the isolation membranes of related technologies struggle to simultaneously achieve high adhesion, high heat resistance, and high ion conductivity.

[0102] During the research process, the inventors of this application made a surprising discovery that by setting a coating including a three-dimensional skeleton structure and organosilicon particles on the surface of the porous substrate of the separator, and by filling at least a portion of the organosilicon particles into the three-dimensional skeleton structure, the separator can achieve high heat resistance, high adhesion and high ion conductivity, and thus enable the secondary battery to achieve high energy density, high thermal stability, long cycle life and good kinetic performance.

[0103] A first aspect of this application provides an isolation membrane comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein the coating comprises a three-dimensional skeleton structure and organosilicon particles, at least a portion of the organosilicon particles filling the three-dimensional skeleton structure.

[0104] The term "three-dimensional skeleton structure" refers to a structure with a three-dimensional spatial shape and a certain amount of porosity, which can be formed by overlapping the materials constituting the three-dimensional skeleton structure.

[0105] The term "organosilicon particles" generally refers to particulate matter formed from siloxane compounds containing -Si-O- structural units.

[0106] The three-dimensional skeleton structure has the advantage of large specific surface area and good affinity with organosilicon particles. It can improve the bonding effect with less binder, thereby reducing the self-discharge of the secondary battery and improving the cycle performance and kinetic performance of the secondary battery.

[0107] At least a portion of the silicone particles are filled into the three-dimensional framework structure, which helps to increase the heat resistance of the separator, reduce the shrinkage of the separator when heated, reduce the risk of short circuit between the positive and negative electrodes, and give the secondary battery high thermal stability. It also maintains high adhesion strength between the coating and the porous substrate, and between the coating and the electrodes (e.g., positive and negative electrodes), thereby reducing the probability of silicone particles detaching during long-term charge-discharge of the secondary battery and improving the interface between the separator and the electrodes. Furthermore, the fact that at least a portion of the silicone particles are filled into the three-dimensional framework structure also gives the separator high porosity and high ion conductivity.

[0108] Meanwhile, compared with traditional inorganic ceramic particles, organosilicon particles have a lower density, which can reduce the weight of secondary batteries and increase their gravimetric energy density.

[0109] Therefore, the separator provided in the embodiments of this application can achieve high heat resistance, high adhesion and high ion conductivity, and thus the secondary battery using it can achieve high energy density, high thermal stability, long cycle life and good kinetic performance.

[0110] In some embodiments, at least a portion of the silicone particles fills the three-dimensional framework structure, and other portions of the silicone particles may be located on the surface of the three-dimensional framework structure and / or at the interface between the three-dimensional framework structure and the porous substrate. Furthermore, at the interface between the three-dimensional framework structure and the porous substrate, a small number of silicone particles may be embedded in the porous substrate. For example, during the winding of the electrode assembly, a small number of silicone particles at the interface may be embedded in the matrix and / or pores of the porous substrate due to external pressure.

[0111] In some embodiments, the volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, in nm; the average diameter of the material constituting the three-dimensional framework structure is denoted as D1, in nm; and the average length of the material constituting the three-dimensional framework structure is denoted as L1, in nm. and

[0112] By adjusting and Within the aforementioned range, it is beneficial for the silicone particles and the three-dimensional skeleton structure to overlap and form an integrated effect, giving the coating a more stable spatial network structure. This can further improve the heat resistance, adhesion and ion conductivity of the separator, and also further improve the thermal stability, cycle performance and kinetic performance of the secondary battery.

[0113] Optionally, This can better improve the heat resistance, adhesion and ion conductivity of the separator, and also better improve the thermal stability, cycle performance and kinetic performance of the secondary battery.

[0114] Optionally, This can better improve the heat resistance, adhesion and ion conductivity of the separator, and also better improve the thermal stability, cycle performance and kinetic performance of the secondary battery.

[0115] In some embodiments, and Optionally, and Alternatively, and This can better improve the heat resistance, adhesion and ion conductivity of the separator, and also better improve the thermal stability, cycle performance and kinetic performance of the secondary battery.

[0116] In some embodiments, the volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, where d1 can be less than or equal to 2000 nm, and can be selected as 275-1500 nm, 350-1500 nm, or 400-1200 nm. A smaller volume distribution particle size Dv50 of the organosilicon particles is beneficial for filling the three-dimensional framework structure, forming a nested effect, and increasing the heat resistance, adhesion, and ion conductivity of the separator.

[0117] In some embodiments, the volume distribution particle size Dv90 of the silicone particles may be less than or equal to 3500 nm, and may be selected as 800-2500 nm. A smaller volume distribution particle size Dv90 of the silicone particles is beneficial for forming a uniform coating.

[0118] The volumetric distribution particle sizes Dv50 and Dv90 are well-known in the art, representing the particle size corresponding to a cumulative volume distribution percentage of 50% and 90%, respectively, and can be determined using instruments and methods known in the art. For example, they can be tested using a laser particle size analyzer (e.g., Master Size 3000) in accordance with GB / T 19077-2016.

[0119] In some embodiments, the morphology of the organosilicon particles may include spherical and / or near-spherical shapes. Spherical and / or near-spherical particle shapes promote good overlap between particles, and the presence of gaps between particles facilitates the construction of a stable spatial network structure, thereby improving the ion transport characteristics and resistance to external extrusion of the separator. Furthermore, the larger gaps between spherical and / or near-spherical particles reduce the impact of the coating on the permeability of the porous substrate, further improving the overall permeability and ion conductivity of the separator, and enhancing the kinetic performance of the secondary battery. Moreover, the larger porosity between spherical and / or near-spherical particles improves the wettability of the separator to the electrolyte, as well as its liquid retention and electrolyte holding capacity, further enhancing the kinetic performance of the secondary battery; moreover, the larger porosity can reduce weight, which is beneficial for increasing the energy density per unit weight of the secondary battery; and it can reduce the amount of organosilicon particles used in the coating, which is beneficial for reducing the cost of the secondary battery.

[0120] The morphology of organosilicon particles can be observed using a scanning electron microscope (SEM). For example, a JSM-5610LV SEM from FEI Corporation in the United States can be used to observe the morphology and structure of the sample after vacuum sputtering with gold.

[0121] In some embodiments, the specific surface area of ​​the organosilicon particles is denoted as S, and its unit is m². 2 / g, 5.0m 2 / g≤S≤12.0m 2 / g, optionally, 6.0m 2 / g≤S≤10.0m 2 / g. When the specific surface area of ​​organosilicon particles is within the above range, it is beneficial for good overlap between particles, making it easier for organosilicon particles to form a porous structure, which is conducive to the migration of active ions.

[0122] The specific surface area of ​​organosilicon particles is a well-known concept in the art and can be determined using instruments and methods known in the field. For example, it can be measured using the nitrogen adsorption specific surface area analysis method according to GB / T 19587-2017, and calculated using the BET (Brunauer Emmett Teller) method. Optionally, the nitrogen adsorption specific surface area analysis can be performed using a Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, Inc.

[0123] In some embodiments, the true density of the organosilicon particles may be 1.0-2.0 g / cm³. 3 The concentration can be selected as 1.2-1.7 g / cm³. 3 .

[0124] When the true density of the silicone particles is within the above range, the compaction density and bulk density of the material increase, which helps to improve the heat resistance of the separator and also helps to reduce coating defects.

[0125] The true density of organosilicon particles is a well-known concept in the art and can be determined using instruments and methods known in the art. For example, referring to GB / T 24586-2009, an inert gas (such as helium or nitrogen) can be used as the medium, and the true volume V of the test sample can be measured using a true density meter via a gas displacement method. t The true density of organosilicon particles = mass of the test sample / true volume of the test sample (V) t .

[0126] In some embodiments, the compacted density of the organosilicon particles at 30000N can be 0.3-1.5 g / cm³. 3 The concentration can be selected as 0.5-1.0 g / cm³. 3 .

[0127] When the compaction density of organosilicon particles is within the above range, the compaction density and bulk density of the material increase, which helps to improve the heat resistance of the separator and also helps to reduce coating defects.

[0128] The compacted density of organosilicon particles is a well-known concept in the art and can be determined using instruments and methods known in the art. For example, it can be determined using an electronic pressure testing machine (e.g., UTM7305) according to GB / T24533-2009. An exemplary test method is as follows: Weigh 1g of material and add it to a container with a bottom area of ​​1.327cm². 2 In the mold, the pressure is increased to 30000N, held for 30s, then depressurized and held for 10s. The compaction density of the material at 30000N is then recorded and calculated.

[0129] In some embodiments, the number-average molecular weight of the silicone particles can be from 20,000 to 80,000, optionally from 25,000 to 70,000, or from 30,000 to 50,000. Exemplarily, the number-average molecular weight of the silicone particles can be 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 80,000, or a range consisting of any two of the above values. When the number-average molecular weight of the silicone particles is within the above range, it is beneficial to form silicone particles with smaller particle sizes, enabling thinner coatings, reducing the overall thickness of the separator, and thus facilitating the improvement of the energy density of the secondary battery. Furthermore, the particle size of the silicone particles formed is not too small, reducing the risk of silicone particles clogging the porous substrate, thereby facilitating the improvement of the overall air permeability and ion conductivity of the separator.

[0130] The number-average molecular weight of organosilicon particles can be determined by gel permeation chromatography (GPC). Specifically, a GPC1515 instrument from Waters Corporation, USA, was used for the determination. The sample was dissolved in tetrahydrofuran for more than 12 hours, the sample concentration was 4 mg / ml, the sample was filtered, and the test temperature was 25℃ with a flow rate of 1 ml / min.

[0131] In some embodiments, the organosilicon particles may include a first structural unit; the first structural unit may have a structure as shown in formula (I):

[0132]

[0133] In equation (I), R 20 To R 27 Each independently comprises one or more of substituted or unsubstituted C1-C10 alkyl groups, structural units as shown in formula (I-1), R 20 To R 27 At least one of them includes the structural unit shown in equation (I-1),

[0134]

[0135] In equation (I-1), R 28 Includes one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R 28 Including hydrogen atoms, or substituted or unsubstituted C1-C3 alkyl groups;

[0136] R 29 Includes substituted or unsubstituted C1-C10 alkyl groups; optionally, R 29 Including substituted or unsubstituted C3-C10 alkyl groups.

[0137] The first structural unit is formed by opening the carbon-carbon double bond of the substituted or unsubstituted acryloyloxy alkyl polysilsesquioxane during the polymerization process. Polysilsesquioxane can be considered as a material containing an organic-inorganic hybrid core-shell structure. Its internal inorganic framework serves as the core, that is, the skeleton structure composed of Si-O-Si or Si-O bonds. Its shell is composed of organic substituents (such as C1-C10 alkyl groups), which wrap around the skeleton structure and are connected to the Si element of the skeleton structure. The core structure of polysilsesquioxane gives organosilicon particles advantages in heat resistance and mechanical properties. Its poor shrinkage allows it to maintain stability during long-term charge-discharge cycles in secondary batteries, effectively isolating the positive and negative electrode plates and thus improving the reliability of secondary batteries. Furthermore, due to the small particle size and large specific surface area of ​​polysilsesquioxane, its physical scale is similar to that of most polymer segments, resulting in high reactivity of atoms on the surface of polysilsesquioxane. Consequently, organosilicon particles exhibit good heat resistance, flame retardancy, and oxidation resistance.

[0138] In some embodiments, the organosilicon particles may include a second and / or a third structural unit in addition to the first structural unit. In these structural units, the hydrogen atoms bonded to the carbon atoms are sometimes omitted and not shown as chemical bonds.

[0139] The second structural unit may have the structure shown in equation (II):

[0140]

[0141] In formula (II), R1 includes one or more of hydrogen atoms and substituted or unsubstituted C1-C5 alkyl groups; optionally, R1 includes one or more of hydrogen atoms and substituted or unsubstituted C1-C3 alkyl groups. R2 includes one or more of substituted or unsubstituted C1-C20 alkyl groups, substituted or unsubstituted C3-C20 cycloalkyl groups, and substituted or unsubstituted C1-C20 hydroxyalkyl groups; optionally, R2 includes one or more of C1-C12 alkyl groups, C3-C12 cycloalkyl groups, and C1-C12 hydroxyalkyl groups.

[0142] The third structural unit may have the structure shown in equation (III):

[0143]

[0144] In formula (III), R3 includes one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; optionally, R3 includes one or more of hydrogen atoms, substituted or unsubstituted C1-C3 alkyl groups.

[0145] The second structural unit may be formed by opening the carbon-carbon double bond of an acrylate-based monomer during the polymerization process. Since the flexible monomer segments in the molecular chain can adjust the glass transition temperature of the silicone particles, improve the toughness and peel strength of the silicone particles, and contribute to exerting a good bonding effect.

[0146] The third structural unit may be formed by opening the carbon-carbon double bond of an acrylonitrile-based monomer during the polymerization process. The third structural unit can provide excellent swelling resistance and high adhesiveness, and help increase the ion conductivity of the secondary battery. When the silicone particles come into contact with the electrolyte, the silicone particles are less prone to swelling and have good swelling resistance.

[0147] Although the above analysis is carried out based on each structural unit, the synergistic effect between the respective structural units cannot be ignored. Specifically, the cooperation of the first structural unit and the second structural unit can exert a synergistic effect to improve the bonding performance and heat resistance of the silicone particles; the cooperation of the second structural unit and the third structural unit can exert a synergistic effect, which can improve the stability and swelling resistance of the silicone particles, etc.

[0148] In some embodiments, the silicone particles include the aforementioned first structural unit, second structural unit and third structural unit at the same time.

[0149] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is denoted as A%, where 0 < A ≤ 20. When the molar content of the first structural unit is within the above range, the heat resistance of the silicone particles can be improved, and its proportion is relatively small, which is beneficial to increasing the proportions of the second structural unit and the third structural unit, and improving the overall properties of the silicone particles such as adhesiveness, stability and swelling resistance. Optionally, 5 ≤ A ≤ 20. Exemplarily, the molar content of the first structural unit may be 5%, 8%, 10%, 12%, 15%, 18%, 20%, or a range formed by any two of the above values.

[0150] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the second structural unit is denoted as B%, where 60 ≤ B < 100. When the molar content of the second structural unit is within the above range, its proportion in the silicone particles is relatively large, which can improve the flexibility of the silicone particles, so that the adhesiveness of the silicone particles is significantly improved; when the silicone particles are applied to a separator, the bonding force between the silicone particles and the base material of the separator can be increased. Optionally, 60 ≤ B ≤ 80. Exemplarily, the molar content of the second structural unit may be 60%, 65%, 70%, 75%, 80%, or a range formed by any two of the above values.

[0151] In some embodiments, based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the third structural unit is denoted as C%, where 0<C≤20. When the molar content of the third structural unit is within the above range, the stability of the silicone particles can be significantly improved. Optionally, 5≤C≤20. Exemplarily, the molar content of the third structural unit may be 5%, 8%, 10%, 12%, 15%, 18%, 20%, or a range formed by any two of the above values.

[0152] The silicone particles include a second structural unit, which endows the silicone particles with good adhesion and flexibility; however, since the silicone particles will inevitably come into contact with the electrolyte when applied to the separator, the swelling effect of the electrolyte will reduce the adhesion of the silicone particles to a certain extent; the silicone particles further include a third structural unit, and the cyano group in the third structural unit can act synergistically with the second structural unit to jointly improve the swelling resistance and adhesion of the silicone particles; especially when the present application further satisfies 3≤B / C≤16, the second structural unit and the third structural unit can exert a more sufficient synergistic effect, improving the adhesion, stability and swelling resistance of the silicone particles. Exemplarily, B / C may be 3, 4, 5, 8, 10, 12, 15, 16, 18, or a range formed by any two of the above values.

[0153] The silicone particles include a second structural unit, which endows the silicone particles with good adhesion, but its own heat resistance is relatively poor. When the silicone particles are applied to a separator, as the charge and discharge time of the secondary battery increases, the temperature inside the secondary battery rises, which may cause damage to the second structural unit; the inorganic structure of polysilsesquioxane in the first structural unit can act synergistically with the second structural unit to improve the overall heat resistance and adhesion performance of the silicone particles; especially when the present application further satisfies 3≤B / A≤16, the first structural unit and the second structural unit can exert a more sufficient synergistic effect, improving the adhesion performance and heat resistance performance of the silicone particles. Exemplarily, B / A may be 3, 4, 5, 8, 10, 12, 15, 16, 18, or a range formed by any two of the above values.

[0154] In some embodiments, B:C:A may be (12 to 16):(1 to 4):(1 to 4). When the molar contents of the first structural unit, the second structural unit and the third structural unit satisfy the above ratio, the three structural units in the silicone particles cooperate with each other to jointly improve the adhesion, stability, swelling resistance and thermal stability of the silicone particles.

[0155] The first structural unit may include multiple chemical structures, and the specific chemical structure of the first structural unit will be described next.

[0156] In some embodiments, R 20 To R 27 Each can independently include structural units as shown in equation (I-1); optionally, R 28 It may include hydrogen atoms, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, or n-pentyl; and / or R 29 It may include n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl or 2-ethylhexyl.

[0157] In some embodiments, R 20 To R 27 One of them may include a structural unit as shown in equation (I-1); optionally, R 28 It may include hydrogen atoms, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, or n-pentyl; and / or R 29 It may include n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl or 2-ethylhexyl.

[0158] The second structural unit may include a variety of chemical structures, and the specific chemical structures of the second structural unit will be described below.

[0159] In some embodiments, R1 may include a hydrogen atom or a methyl group.

[0160] In some embodiments, R2 may include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-octyl, isooctyl, 2-ethylhexyl, dodecyl, or isobornyl.

[0161] For example, the second structural unit may include one or more of the structures shown in equation (II-1) to (II-8):

[0162]

[0163] The third structural unit may include a variety of chemical structures, and the specific chemical structures of the third structural unit will be described below.

[0164] In some embodiments, R3 may include a hydrogen atom or a methyl group.

[0165] For example, the third structural unit may include one or more of the structures shown in equation (III-1) to (III-4):

[0166]

[0167]

[0168] The types of functional groups in organosilicon particles can be determined using infrared spectroscopy. For example, the infrared spectrum of the material can be tested to identify its characteristic peaks, thereby determining the types of modified functional groups. Specifically, the material can be subjected to infrared spectral analysis using instruments and methods known in the art, such as an infrared spectrometer (e.g., the Nicolet IS10 Fourier transform infrared spectrometer) and tested according to the General Rules for Infrared Spectroscopic Analysis in GB / T 6040-2019.

[0169] In some embodiments, the infrared spectrum of the organosilicon particles has a wavelength of 1100 nm. -1 Up to 1120cm -1 The characteristic peak indicates the presence of a Si-O-Si framework of sesquioxane.

[0170] In some embodiments, the infrared spectrum of the organosilicon particles has a 1750 cm⁻¹ area. -1 Up to 1735cm -1 The characteristic peak indicates the presence of an ester group.

[0171] In some embodiments, the infrared spectrum of the organosilicon particles has a 2260 cm⁻¹. -1 Up to 2220cm -1 The characteristic peak indicates the presence of a cyano group.

[0172] In some embodiments, the organosilicon particles may include the structural unit shown in formula (a):

[0173]

[0174] In equation (a), R 14 and R 15 Each is independently selected from hydrogen atoms, substituted or unsubstituted C1-C10 alkyl, hydroxyl, or amino groups; optionally, R 14 and R 15 Each is independently selected from hydrogen atoms, substituted or unsubstituted C1-C6 alkyl, hydroxyl or amino atoms.

[0175] Optionally, the organosilicon particles may include one or more of polymethylsiloxane, polydimethylsiloxane, polydiethylsiloxane, polymethylhydroxysiloxane, polymethylaminosiloxane, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or groups of atoms in a polymer by other atoms or groups of atoms.

[0176] In some embodiments, the content of the silicone particles may be greater than or equal to 50 wt%, optionally 50-90 wt% or 50-88 wt%, based on the total weight of the coating. When the content of silicone particles is within the above range, the overall adhesion, stability, swelling resistance, and heat resistance of the separator can be further improved.

[0177] In some embodiments, the content of the three-dimensional skeleton structure may be less than 50 wt%, and may be 8-48 wt% or 10-48 wt%, based on the total weight of the coating.

[0178] In some embodiments, the material constituting the three-dimensional framework structure may include at least one of wires, rods, tubes, and bars. Materials of suitable shapes facilitate the formation of a more stable spatial network structure between the three-dimensional framework structure and the silicone particles, thereby further improving the heat resistance, ion conductivity, and electrolyte wetting and retention properties of the separator.

[0179] In some embodiments, the average diameter of the material constituting the three-dimensional framework structure is denoted as D1, which may be less than or equal to 50 nm, and may be selected as 4-45 nm, 4-42 nm, 10-42 nm, or 16-40 nm. When the average diameter of the material constituting the three-dimensional framework structure is within the above range, the ion conductivity and voltage breakdown resistance of the separator can be further improved, and it also helps to form an integrated effect with the organosilicon particles, thereby further improving the heat resistance of the separator.

[0180] In some embodiments, the average length of the material constituting the three-dimensional framework structure is denoted as L1, which can be 100-3500 nm, and optionally 400-3000 nm, 500-3000 nm, 600-3000 nm, or 700-3000 nm. When the average length of the material constituting the three-dimensional framework structure is within the above range, the heat resistance and ion conductivity of the separator can be further improved.

[0181] In some embodiments, the aspect ratio of the material constituting the three-dimensional framework structure can be from 5 to 150, and can be selected as 12 to 120, 20 to 100, 30 to 95, or 40 to 90. When the aspect ratio of the material constituting the three-dimensional framework structure is within the above range, the ion conductivity of the separator and its wetting and retention properties with the electrolyte can be further improved.

[0182] The average length and average diameter of the material constituting the three-dimensional framework structure can be determined using the following method: A 3.6 mm × 3.6 mm sample is cut from any region of the isolation membrane. The microstructure of the coating in the sample is mapped using a scanning electron microscope (e.g., ZEISS Sigma300). A high vacuum mode is selected, with a working voltage of 3 kV and a magnification of 30,000x to obtain a SEM image. Based on the obtained SEM image, multiple (e.g., more than 5) test regions are selected for length statistics. Each test region has a size of 0.5 μm × 0.5 μm. The average length of each test region is then taken as the average length of the material constituting the three-dimensional framework structure. Based on the obtained SEM image, multiple (e.g., more than 5) test regions are selected for diameter statistics using Nano Measurer particle size distribution statistical software. Each test region has a size of 0.5 μm × 0.5 μm. The average diameter of each test region is then taken as the average diameter of the material constituting the three-dimensional framework structure.

[0183] When the material constituting the three-dimensional framework structure includes nanocellulose, since the diameters at both ends of the nanocellulose length direction are usually smaller and the diameter in the middle is usually larger, the maximum diameter in the length direction of the nanocellulose can be taken as the diameter of the nanocellulose. The diameters of other nanocelluloses can be processed in a similar way. Then, the average diameter of the nanocellulose can be obtained using Nano Measurer particle size distribution statistical software as described above.

[0184] In some embodiments, the material constituting the three-dimensional skeleton structure may include at least one of organic and inorganic materials.

[0185] Optionally, the organic material may include at least one of cellulose nanofibers, polytetrafluoroethylene nanofibers, and polyamide nanofibers.

[0186] Optionally, the inorganic material may include at least one of halloysite nanotubes, nanorod alumina, nanorod boehmite, nanorod silica, and glass fiber.

[0187] The materials constituting the three-dimensional skeleton structure are rich in hydroxyl groups, which can easily bond with organosilicon particles and porous substrates. This can improve the bonding effect with less binder, reduce the self-discharge of the secondary battery, and improve the cycle performance and kinetic performance of the secondary battery. It can also form a stable coating structure, which can improve the heat resistance and ion conductivity of the secondary battery.

[0188] In some embodiments, the material constituting the three-dimensional framework structure may include nanocellulose. Optionally, the nanocellulose may include at least one of cellulose nanofibrils (CNF, also known as nanofibrillated cellulose or microfibrillated cellulose), cellulose nanocrystals (CNC, also known as cellulose nanocrystals or nanocrystalline cellulose), and bacterial nanocellulose (BNC, also known as bacterial cellulose or microbial cellulose).

[0189] Nanocellulose refers to cellulose with any dimension within the nanometer range (e.g., within 100 nm), possessing both the characteristics of cellulose and those of nanoparticles. Nanocellulose can be a high-molecular-weight nanomaterial extracted from natural sources such as wood and cotton through one or more chemical, physical, or biological methods. It boasts advantages such as wide availability, low cost, biodegradability, high modulus, and high specific surface area, making it an excellent alternative to traditional petrochemical resources and effectively alleviating environmental pollution and petrochemical resource shortages. Nanocellulose also exhibits excellent high-temperature resistance and minimal volume change upon heating, thereby improving the heat resistance of the separator. Furthermore, compared to traditional inorganic ceramic particles, nanocellulose has a lower density, which can reduce the weight of the secondary battery and increase its gravimetric energy density. In addition, the three-dimensional framework structure formed by nanocellulose can possess tiny nanopores to prevent current leakage, enabling the separator to maintain both good electrolyte wetting and retention properties and excellent voltage breakdown resistance.

[0190] In some embodiments, the nanocellulose may include at least one of unmodified nanocellulose (also known as hydroxy nanocellulose) and modified nanocellulose, optionally modified nanocellulose.

[0191] Modified nanocellulose refers to nanocellulose that simultaneously includes hydroxyl groups and modified groups. In some embodiments, the modified nanocellulose includes modified groups, and the modified groups may include at least one selected from amino, carboxyl, aldehyde, sulfonic acid, boric acid, and phosphate groups, and optionally include at least one selected from sulfonic acid, boric acid, and phosphate groups.

[0192] When nanocellulose possesses the aforementioned specific modifying groups, it can effectively improve the heat resistance of the separator and enhance the thermal stability of the secondary battery. Furthermore, it can strengthen the bond between the coating and the porous substrate. The presence of these specific modifying groups also facilitates the integration of nanocellulose with organosilicon particles, resulting in a more stable spatial network structure in the coating. This enhances the separator's wetting and retention properties with the electrolyte, improving its ion conductivity and voltage breakdown resistance. In addition, the presence of these modifying groups reduces the proportion of hydroxyl groups, allowing the coating slurry to have a suitable viscosity, which is more conducive to coating application, thereby improving the separator's production efficiency and coating uniformity.

[0193] In some embodiments, the molar ratio of the modified group to the hydroxyl group can be 1:4 to 4:1, and optionally 2:3 to 7:3. When the molar ratio of the modified group to the hydroxyl group is within the above range, the heat resistance, ion conductivity, and electrolyte wetting and retention characteristics of the separator can be further improved. Furthermore, it can effectively avoid the following situations: when the molar ratio of the modified group to the hydroxyl group is too small, the further improvement effect of the modified group on the heat resistance and ion conductivity of the separator may not be significant; when the molar ratio of the modified group to the hydroxyl group is too large, the electrolyte wetting and retention characteristics of the separator may deteriorate, which may affect the cycle performance and reliability of the secondary battery, and may also lead to a decrease in the heat resistance of the separator, which may further affect the improvement effect on the thermal stability of the secondary battery.

[0194] The types of modifying groups in nanocellulose can be determined using infrared spectroscopy. For example, the infrared spectrum of the material can be tested to identify its characteristic peaks, thereby determining the types of modifying groups. Specifically, the material can be analyzed using infrared spectroscopy with instruments and methods known in the art, such as an infrared spectrometer (e.g., the Nicolet IS10 Fourier transform infrared spectrometer) according to the General Rules for Infrared Spectroscopic Analysis in GB / T 6040-2019.

[0195] In some embodiments, the material constituting the three-dimensional framework structure includes sulfonic acid groups, and the sulfur content in the material constituting the three-dimensional framework structure may be ≥0.1 wt%, optionally 0.2-0.5 wt%, based on the total weight of the material constituting the three-dimensional framework structure. Optionally, the material constituting the three-dimensional framework structure may include nanocellulose.

[0196] The sulfur content in the material constituting the three-dimensional framework structure can be determined as follows: After drying the material, grind it in a mortar (such as an agate mortar) for 30 minutes, and then use an X-ray diffractometer (such as a Miniflex 600-C) to determine the sulfur content. The test can be performed using a Cu target, a Ni filter, a tube voltage of 40 kV, a tube current of 15 mA, and a continuous scanning range of 5°–80°.

[0197] In some embodiments, the coating may further include a non-particulate binder. This application does not impose particular limitations on the type of non-particulate binder; any known material with good adhesion can be selected. Optionally, the non-particulate binder may include at least one of polyacrylonitrile, acrylic resins, acrylate resins, polyvinyl alcohol, isobutylene-maleic anhydride copolymer, polyacrylamide, sodium carboxymethyl cellulose, carboxymethyl chitosan, sodium alginate, and their respective derivatives. Derivatives generally refer to products derived from which hydrogen atoms or groups in a polymer are replaced by other atoms or groups.

[0198] In some embodiments, the content of the non-particulate binder in the coating may be ≤5 wt%, based on the total weight of the coating.

[0199] In some embodiments, the thickness of the coating may be ≤4μm, optionally 0.4-3μm. This application enables thin coating application, reduces the overall thickness of the separator, and helps to improve the energy density of the secondary battery.

[0200] In some embodiments, the thickness of the porous substrate may be ≤6 μm, optionally 3-5 μm. The coating of this application can significantly improve the heat resistance of the separator, thereby allowing for the use of a thinner porous substrate, which helps to improve the energy density of the secondary battery.

[0201] This application does not impose any particular limitation on the material of the porous substrate; any known substrate with good chemical and mechanical stability can be selected. For example, the porous substrate may include at least one of porous polyolefin-based resin membranes (e.g., polyethylene, polypropylene, polyvinylidene fluoride), porous glass fiber, and porous nonwoven fabric. The porous substrate may be a single-layer film or a multi-layer composite film. When the porous substrate is a multi-layer composite film, the materials of each layer may be the same or different.

[0202] In some embodiments, the longitudinal thermal shrinkage rate of the separator at 150°C for 1 hour may be ≤4.5%, and may be 0.8%-3%.

[0203] In some embodiments, the transverse thermal shrinkage rate of the separator at 150°C for 1 hour may be ≤4.5%, and may be 1%-3%.

[0204] The separator exhibits low thermal shrinkage in both the transverse and longitudinal directions at a high temperature of 150°C, thereby improving the reliability of the secondary battery.

[0205] In some embodiments, the longitudinal tensile strength of the separator may be ≥1600 kg / cm². 2 Available in 1800-4500 kg / cm² 2 .

[0206] In some embodiments, the transverse tensile strength of the separator may be ≥1600 kg / cm². 2 Available in 1800-4500 kg / cm² 2 .

[0207] The separator has high tensile strength in both the transverse and longitudinal directions, which reduces the probability of damage when the secondary battery expands, thereby improving the reliability of the secondary battery.

[0208] In some embodiments, the wetting length of the separator may be ≥20mm, and may be 30-80mm.

[0209] In some embodiments, the wetting rate of the separator membrane can be ≥2 mm / s, and can be selected as 3-10 mm / s.

[0210] The separator has good wetting and retention properties for electrolyte, which can improve the ion conductivity of the separator and the capacity of the secondary battery.

[0211] In some embodiments, the air permeability of the separator can be ≤350s / 100mL, optionally 100-270s / 100mL. The separator exhibits good air permeability, thereby improving ion conductivity and the capacity performance of the secondary battery.

[0212] In some embodiments, the ion conductivity of the separator may be ≥0.5 mS / cm, and may be selected as 0.55-0.98 mS / cm.

[0213] The heat shrinkage rate, tensile strength, and air permeability of the separator have meanings known in the art and can be measured using methods known in the art. For example, they can all be tested according to GB / T 36363-2018.

[0214] The wetting length and wetting speed of the separator are well-known in the art and can be measured using methods known in the art. An exemplary test method is as follows: Cut the separator into samples with a width of 5 mm and a length of 100 mm, fix both ends of the sample, and place it horizontally; drop 0.5 mg of electrolyte into the center of the sample, and after a specified time (1 min in this application), take a photograph and measure the length of electrolyte diffusion, thereby obtaining the wetting length and wetting speed of the separator. For accuracy, multiple samples (e.g., 5 to 10) can be tested, and the test results are obtained by calculating the average value. The electrolyte can be prepared as follows: Mix ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a mass ratio of 30:50:20 to obtain an organic solvent, and dissolve fully dried LiPF6 in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0215] The ionic conductivity of the separator can be obtained by electrochemical impedance spectroscopy. Specifically, the separator is cut into circular pieces of a certain area, dried, and placed between two stainless steel electrodes. After absorbing a sufficient amount of electrolyte, it is sealed to form a coin cell, and then subjected to AC impedance spectroscopy.

[0216] It should be noted that the coating parameters (such as thickness) of the aforementioned separator are coating parameters for one side of the porous substrate. When the coating is applied to both sides of the porous substrate, if the coating parameters on either side meet the requirements of this application, it is considered to fall within the protection scope of this application.

[0217] Preparation method

[0218] The second aspect of this application provides a method for preparing a separator membrane according to the first aspect of this application, comprising the following steps: providing a porous substrate; kneading organosilicon particles with a binder, adding a material for forming a three-dimensional skeleton structure and a solvent, mixing uniformly to prepare a coating slurry; coating the coating slurry onto at least one surface of the porous substrate, and drying to obtain a separator membrane, wherein the separator membrane comprises a porous substrate and a coating disposed on at least one surface of the porous substrate, the coating comprising a three-dimensional skeleton structure and organosilicon particles, at least a portion of the organosilicon particles filling the three-dimensional skeleton structure.

[0219] In the preparation method provided in the embodiments of this application, the organosilicon particles are first kneaded with a binder, and then a material constituting a three-dimensional skeleton structure (such as at least one of wires, rods, tubes and bars) is added, thereby forming a three-dimensional skeleton structure, and at least a portion of the organosilicon particles are filled in the three-dimensional skeleton structure.

[0220] Organosilicon particles comprising the structural unit shown in formula (a) are commercially available.

[0221] Organosilicon particles comprising a first structural unit, a second structural unit, and / or a third structural unit can be obtained according to the preparation method provided in the embodiments of this application.

[0222] In some embodiments, the method for preparing organosilicon particles may include the following steps: providing a first monomer, a second monomer, and / or a third monomer; mixing the first monomer, the second monomer, and / or the third monomer, and performing a polymerization reaction under the action of an initiator to generate organosilicon particles.

[0223] The first monomer, the second monomer, and the third monomer are used to form the first structural unit, the second structural unit, and the third structural unit as described above in this application, respectively.

[0224] For example, the first monomer may include one or more of the following: methacryloxypropyl cage-type polysilsesquioxane, methacryloxypropyl heptaisobutyl polysilsesquioxane, methacryloxypropyl heptaoctyl polysilsesquioxane, acryloxypropyl cage-type polysilsesquioxane, acryloxypropyl heptaisobutyl polysilsesquioxane, and methacryloxypropyl heptaoctyl polysilsesquioxane.

[0225] For example, the second monomer may include one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.

[0226] For example, the third monomer may include acrylonitrile and / or methacrylonitrile.

[0227] In some embodiments, the step of mixing the first monomer, the second monomer, and / or the third monomer and undergoing polymerization under the action of an initiator to generate organosilicon particles may specifically include: adding the first monomer, the second monomer, and / or the third monomer to a solvent and an emulsifier and mixing them to form a mixed system; adding an initiator to the mixed system and undergoing polymerization under the action of the initiator to generate organosilicon particles.

[0228] This application demonstrates the copolymerization of multiple monomers via emulsion polymerization, a simpler polymerization method. Of course, other polymerization methods can also be used, such as solution polymerization and suspension polymerization. The process parameters employed in the polymerization process can be those commonly used in the field, and will not be elaborated upon here.

[0229] In some embodiments, the emulsifier may include one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, alkyl diphenyl oxide disulfonate, and ethoxylated alkylphenol ammonium sulfate.

[0230] In some embodiments, the mass percentage of the emulsifier may be from 0.1% to 5% based on the total mass of the first monomer, the second monomer, and the third monomer. When the mass percentage of the emulsifier is within the above range, the first monomer, the second monomer, and the third monomer can be emulsified and dispersed in the solvent to form a relatively homogeneous system.

[0231] In some embodiments, the initiator may include potassium persulfate and / or ammonium persulfate.

[0232] In some embodiments, the initiator mass percentage may be from 0.15% to 1% based on the total mass of the first monomer, the second monomer, and the third monomer. An initiator mass percentage within this range contributes to sufficient polymerization.

[0233] In some embodiments, the solvent may include water, such as deionized water.

[0234] As a specific embodiment, the preparation method of organosilicon particles may include: mixing deionized water, emulsifier, first monomer, second monomer and / or third monomer evenly to obtain a prepolymer solution; adding emulsifier and deionized water to a container, stirring and emulsifying for 30 min to 60 min to obtain a uniform and stable emulsion; then slowly adding the emulsion dropwise to the prepolymer solution and the initiator solution (for example, potassium persulfate and / or ammonium persulfate can be dissolved in deionized water to form a solution); after the dropwise addition is completed, heating to 90°C to 110°C and holding the temperature for 0.5 h, cooling to 40°C, adjusting the pH to 7 to 8 with ammonia water, filtering, discharging, and drying to obtain organosilicon particles.

[0235] In some embodiments, the solvent used when preparing the coating slurry may be water, such as deionized water.

[0236] In some embodiments, the coating slurry may also include other components, such as dispersants, wetting agents, binders, etc.

[0237] In some embodiments, the material used to constitute the three-dimensional framework structure may include at least one of organic and inorganic materials. Optionally, the organic material may include at least one of cellulose nanofibers, polytetrafluoroethylene nanofibers, and polyamide nanofibers. Optionally, the inorganic material may include at least one of halloysite nanotubes, nanorod-shaped alumina, nanorod-shaped boehmite, nanorod-shaped silica, and glass fiber.

[0238] In some embodiments, the material constituting the three-dimensional framework structure may include nanocellulose.

[0239] In some embodiments, nanocellulose can be obtained by the following method: providing cellulose powder with a whiteness ≥80%; mixing and reacting the obtained cellulose powder with a modification solution, washing to remove impurities, adjusting the pH to neutral, and then grinding and cutting to obtain nanocellulose.

[0240] Optionally, the cellulose powder with a whiteness ≥80% can be obtained commercially or by chemical methods (e.g., acid hydrolysis, alkali treatment, Tempo catalytic oxidation), biological methods (e.g., enzymatic treatment), or mechanical methods (e.g., ultrafine grinding, ultrasonic crushing, high-pressure homogenization). The fiber raw materials used to prepare the cellulose powder with a whiteness ≥80% may include at least one of plant fibers, such as cotton fibers (e.g., cotton fiber, kapok fiber), hemp fibers (e.g., sisal fiber, ramie fiber, jute fiber, flax fiber, hemp fiber, abaca fiber, etc.), palm fiber, wood fiber, bamboo fiber, and grass fiber.

[0241] In some embodiments, the cellulose powder with a whiteness of ≥80% can also be prepared by the following method: after the fiber raw material is opened and slag is removed, it is cooked with an alkaline solution (e.g., an aqueous solution of NaOH, the concentration of which can be 4wt% to 20wt%, optionally 5wt% to 15wt%), and then sequentially subjected to water washing to remove impurities (e.g., water washing 3 to 6 times), bleaching (e.g., sodium hypochlorite and / or hydrogen peroxide can be used), acid washing to remove impurities, water washing to remove impurities, water removal, and air drying to obtain cellulose powder.

[0242] In some embodiments, the modified solution may be an acid solution (e.g., aqueous sulfuric acid solution, aqueous boric acid solution, aqueous phosphoric acid solution, aqueous acetic acid solution) or an alkaline solution (e.g., urea organic solvent solution). Optionally, the modified solution is an acid solution.

[0243] Optionally, the concentration of the acid solution can be from 5 wt% to 80 wt%. When the modifying solution is an aqueous sulfuric acid solution, the concentration of the acid solution can be from 40 wt% to 80 wt%, thereby obtaining cellulose powder with sulfonic acid groups. When the modifying solution is an aqueous boric acid solution, the concentration of the acid solution can be from 5 wt% to 10 wt%, thereby obtaining cellulose powder with boric acid groups. When the modifying solution is an aqueous phosphoric acid solution, the concentration of the acid solution can be from 45 wt% to 75 wt%, thereby obtaining cellulose powder with phosphoric acid groups. When the modifying solution is an aqueous acetic acid solution, the concentration of the acid solution can be from 40 wt% to 80 wt%, thereby obtaining cellulose powder with carboxylic acid groups.

[0244] Optionally, the urea organic solvent solution can be a urea xylene solution, thereby obtaining cellulose powder with amine groups.

[0245] In some embodiments, the mass ratio of cellulose powder to modified solution may optionally be 1:2.5 to 1:50, or optionally 1:5 to 1:30.

[0246] When sulfuric acid aqueous solution is used as the modifying solution, the mass ratio of cellulose powder to acid solution can be 1:5 to 1:30. When boric acid aqueous solution is used as the modifying solution, the mass ratio can be 1:20 to 1:50. When phosphoric acid aqueous solution is used as the modifying solution, the mass ratio can be 1:5 to 1:30. When acetic acid aqueous solution is used as the modifying solution, the mass ratio can be 1:5 to 1:30. When urea organic solvent solution is used as the modifying solution, the mass ratio can be 1:4 to 1:40.

[0247] In some embodiments, when the modified solution is an acidic solution, the reaction can be carried out at a temperature not exceeding 80°C, preferably at a temperature between 30°C and 60°C, and the reaction time between the cellulose powder and the modified solution can be 0.25 h to 3 h, preferably 0.5 h to 1.8 h.

[0248] In some embodiments, when the modified solution is an alkaline solution, the reaction can be carried out at 100°C to 145°C, and the reaction time between the cellulose powder and the modified solution can be 0.5 h to 3.5 h.

[0249] In some embodiments, grinding can be performed using a grinding machine, and cutting can be performed using a high-pressure homogenizer. By adjusting the grinding parameters of the grinding machine (e.g., grinding times, grinding time, etc.) and the cutting parameters of the high-pressure homogenizer, nanocellulose with different average diameters and / or different average lengths can be obtained.

[0250] In some embodiments, a coating machine may be used to apply the coating slurry. This application does not impose any particular limitation on the type of coating machine; for example, a commercially available coating machine may be used. The coating machine includes a gravure roller; the gravure roller is used to transfer the slurry onto a porous substrate.

[0251] In some embodiments, the coating slurry can be applied by transfer coating, spin coating, dip coating, etc.

[0252] The raw materials and their content parameters used in the preparation method of the separator membrane can be referred to the separator membrane of the first aspect of the present application, and will not be repeated here.

[0253] Unless otherwise specified, all raw materials used in the preparation of the separator membrane can be obtained commercially.

[0254] Secondary batteries

[0255] The third aspect of this application provides a secondary battery.

[0256] A secondary battery, also known as a rechargeable battery or accumulator, is a battery that can be recharged after discharge to reactivate its active materials and continue to be used. Typically, a secondary battery consists of an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator. The separator is positioned between the positive and negative electrodes and primarily serves to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through.

[0257] This application does not impose any particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, a sodium-ion battery, a lithium metal battery, a sodium metal battery, etc. In particular, the secondary battery can be a lithium-ion battery.

[0258] The secondary battery of the third aspect of this application includes a separator membrane of the first aspect of this application or a separator membrane prepared by the method of the second aspect of this application, wherein the separator membrane is spaced between the positive electrode and the negative electrode. Optionally, at least the side of the separator membrane closest to the negative electrode has the coating of this application. Thus, the secondary battery of this application can achieve high energy density, high thermal stability, long cycle life and good kinetic performance.

[0259] [Positive electrode plate]

[0260] In some embodiments, the positive electrode may include a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector and comprising a positive electrode active material. For example, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0261] When the secondary battery is a lithium-ion battery, the positive electrode active material may include, but is not limited to, at least one of lithium transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and their respective modified compounds. Examples of lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and their respective modified compounds.

[0262] In some embodiments, to further improve the energy density of secondary batteries, the positive electrode active material for lithium-ion batteries may include materials with the general formula Li. a Ni b Co c M d O e Af At least one of lithium transition metal oxides and their modified compounds. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from at least one of N, F, S and Cl.

[0263] As an example, positive electrode active materials for lithium-ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.

[0264] When the secondary battery is a sodium-ion battery, the positive electrode active material may include, but is not limited to, at least one of sodium-containing transition metal oxides, polyanionic materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.

[0265] As an example, positive electrode active materials for sodium-ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, and NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, with the general formula X p M' q (PO4) r O x Y 3-x At least one of the materials in general formula X.p M' q (PO4) r O x Y 3-x In the given information, 0 < p ≤ 4, 0 < q ≤ 2, 1 ≤ r ≤ 3, 0 ≤ x ≤ 2, and X is selected from H. + Li + Na + K + and NH4 + At least one of the following, M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halide anion, optionally at least one of F, Cl and Br.

[0266] The modified compounds for the above-mentioned positive electrode active materials can be obtained by doping and / or surface coating of the positive electrode active materials.

[0267] In some embodiments, the positive electrode film may optionally include a positive electrode conductive agent. This application does not impose any particular limitation on the type of positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0268] In some embodiments, the positive electrode film layer may optionally include a positive electrode binder. This application does not impose any particular limitation on the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.

[0269] In some embodiments, the positive current collector may be a metal foil or a composite current collector. An example of a metal foil is aluminum foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. An example of a metal material may be at least one selected from aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. An example of a polymer substrate may be at least one selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0270] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder, and any other components in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP), but is not limited to it.

[0271] [Negative electrode plate]

[0272] In some embodiments, the negative electrode sheet may include a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector and comprising a negative electrode active material. For example, the negative current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.

[0273] The negative electrode active material may be any negative electrode active material known in the art for use in secondary batteries. As an example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include at least one of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide, and tin alloys.

[0274] In some embodiments, the negative electrode film layer may optionally include a negative electrode conductive agent. This application does not impose any particular limitation on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0275] In some embodiments, the negative electrode film layer may optionally include a negative electrode binder. This application does not impose any particular limitation on the type of negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0276] In some embodiments, the negative electrode film may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc.

[0277] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. As an example, the metal material may include at least one of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymeric material substrate may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0278] The negative electrode film is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.

[0279] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet also includes a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode sheet of this application also includes a protective layer covering the surface of the negative electrode film layer.

[0280] Electrolyte

[0281] During the charging and discharging process of a secondary battery, active ions repeatedly insert and extract between the positive and negative electrode plates, while the electrolyte acts as a conductor for these active ions. This application does not impose any particular restrictions on the type of electrolyte; it can be selected according to actual needs.

[0282] Electrolytes consist of electrolyte salts and solvents. The types of electrolyte salts and solvents are not specifically limited and can be selected according to actual needs.

[0283] When the secondary battery is a lithium-ion battery, as an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0284] When the secondary battery is a sodium-ion battery, as an example, the electrolyte salt may include, but is not limited to, at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), sodium dioxalate borate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorodioxalate phosphate (NaDFOP), and sodium tetrafluorooxalate phosphate (NaTFOP).

[0285] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0286] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, additives that improve battery low-temperature power performance, etc.

[0287] In some embodiments, the positive electrode, the separator, and the negative electrode can be fabricated into an electrode assembly by a winding process and / or a stacking process.

[0288] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0289] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0290] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. Figure 1 This is an example of a square-structured secondary battery 5.

[0291] In some embodiments, such as Figure 2 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process and / or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The secondary battery 5 may contain one or more electrode assemblies 52, which can be adjusted according to requirements.

[0292] Methods for preparing secondary batteries are well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding process and / or a stacking process. The electrode assembly is placed in an outer package, dried, and then injected with an electrolyte. After vacuum sealing, settling, formation, and shaping processes, a secondary battery is obtained.

[0293] In some embodiments, the secondary battery according to this application can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module.

[0294] Figure 3 This is a schematic diagram of battery module 4 as an example. Figure 3 As shown, in battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.

[0295] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.

[0296] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0297] Figure 4 and Figure 5 This is a schematic diagram of battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0298] Electrical appliances

[0299] A fourth aspect of this application provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the embodiments of this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit of the electrical device. The electrical device can be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0300] Electrical devices can be equipped with secondary batteries, battery modules, or battery packs depending on their usage requirements.

[0301] Figure 6 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.

[0302] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.

[0303] Example

[0304] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0305] Preparation of nanocellulose

[0306] After the cotton linters are opened and the slag is removed by a cotton opener, they are cooked at 150°C for 2 hours using a 5wt% NaOH aqueous solution. Then, the cotton cellulose powder with a whiteness of ≥85% is obtained by sequentially washing and removing impurities (washing 3 times), bleaching with sodium hypochlorite, washing and removing impurities with dilute hydrochloric acid, washing and removing impurities (washing 1 time), water removal, and air drying.

[0307] 1 kg of the obtained cotton cellulose powder was mixed with 30 kg of 60 wt% sulfuric acid aqueous solution and reacted at 55℃ to 60℃ for 0.5 h to 0.8 h. After the reaction was completed, the mixture was washed with water to remove impurities (washed 3 times), filtered, and deacidified and depurified. The pH was then adjusted to neutral with 10 wt% NaOH aqueous solution. The mixture was then ground with a grinder and then nano-cut using a high-pressure homogenizer to obtain nanocellulose with sulfonic acid modified groups. The molar ratio of sulfonic acid groups to surface hydroxyl groups was between 2:3 and 7:3.

[0308] During the preparation process, nanocellulose with different average diameters and / or different average lengths can be obtained by adjusting the reaction concentration, reaction time, grinding mill parameters, and cutting parameters of high-pressure homogenizer.

[0309] The molar ratio of modified groups to surface hydroxyl groups in nanocellulose can be determined by the following method: The hydroxyl values ​​(equivalent to milligrams of potassium hydroxide per gram of sample) of the raw cellulose and nanocellulose are tested according to the phthalic anhydride method in GB / T12008.3-2009. The resulting values ​​are in mg KOH / g, which are then converted to mmol / g as the hydroxyl content. The content of modified groups (i.e., the content of modified hydroxyl groups) is obtained by subtracting the hydroxyl content of nanocellulose from the hydroxyl content of the raw cellulose. The molar ratio of modified groups to hydroxyl groups can then be calculated.

[0310] Example 1

[0311] Preparation of the separating membrane

[0312] Porous PE substrate is available: 4.7μm thick.

[0313] Preparation of organosilicon particles

[0314] 1400g of deionized water and 7g of sodium dodecyl sulfate were added to a 5L three-necked flask and stirred and emulsified at 1500r / min for 30min to obtain a uniform and stable emulsion. Then, 645.68g of methyl acrylate, 79.59g of acrylonitrile and 663.50g of methacryloyloxypropyl cage-type polysilsesquioxane (the molar ratio of methyl acrylate, acrylonitrile and methacryloyloxypropyl cage-type polysilsesquioxane was 15:3:2) were added in sequence, and stirring was continued at 1500r / min for 30min to obtain a uniform prepolymer.

[0315] In a dry three-necked flask, 3g of emulsifier and 1000g of deionized water were added and emulsified at high speed for 30 minutes to obtain a uniform and stable emulsion. Then, the prepolymer and initiator solution prepared in the previous step were slowly added dropwise using a peristaltic pump (3g of potassium persulfate initiator was dissolved in 30g of deionized water to form a solution). After the addition was completed, the temperature was raised to 90℃ and kept at that temperature for 0.5h. After cooling to 40℃, the pH was adjusted to 7-8 with ammonia water, filtered, discharged, and dried to obtain organosilicon particles.

[0316] Preparation of the coating slurry: After kneading the prepared organosilicon particles with the binder acrylic resin, nanocellulose and an appropriate amount of deionized water are added and mixed evenly to obtain the coating slurry. The mass ratio of organosilicon particles, nanocellulose, and binder is 85:11:4.

[0317] Coating: The prepared coating slurry is coated onto the two surfaces of the PE porous substrate using a coating machine, and the release film is obtained through drying and slitting processes.

[0318] Preparation of positive electrode sheet

[0319] LiNi, the positive electrode active material 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry. The positive electrode slurry is coated onto the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.

[0320] Preparation of negative electrode sheet

[0321] Artificial graphite (anode active material), carbon black (Super P) (conductive agent), styrene-butadiene rubber (SBR) (binder), and sodium carboxymethyl cellulose (CMC) (batch ratio 96.4:0.7:1.8:1.1) are mixed evenly in an appropriate amount of deionized water to obtain a cathode slurry. The cathode slurry is coated onto copper foil (cathode current collector), and the cathode sheet is obtained through drying, cold pressing, slitting, and cutting processes.

[0322] Preparation of electrolyte

[0323] Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 30:30:40 to obtain an organic solvent. Fully dried LiPF6 was dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0324] Preparation of secondary batteries

[0325] The positive electrode, separator, and negative electrode are stacked and wound in sequence to obtain the electrode assembly. The electrode assembly is placed in the outer packaging aluminum-plastic film, dried, and then injected with electrolyte. After vacuum sealing, standing, formation, and shaping, a small soft-pack secondary battery with a capacity of 4240mAh is obtained.

[0326] Example 2-13

[0327] The secondary battery was prepared using a method similar to that in Example 1, except that the volume distribution particle size Dv50 of the organosilicon particles and / or the average diameter and average length of the nanocellulose used in the preparation of the separator were different. Specific parameters are detailed in Tables 1 and 2. The volume distribution particle size Dv50 of the organosilicon particles can be adjusted by physical shearing methods such as grinding and high-speed dispersion.

[0328] Examples 14-20

[0329] The secondary batteries were prepared using a method similar to that of Example 1, except that the organosilicon particles used in the preparation of the separator were different. The organosilicon particles used in Examples 13-19 were prepared using a method similar to that of Example 1, except that at least one of the raw material components and contents was adjusted. The relevant parameters are shown in Tables 1 and 2.

[0330] Examples 21-25

[0331] The secondary battery was prepared using a method similar to that in Example 1, except that the content of organosilicon particles and / or nanocellulose used in the preparation of the separator was different. For specific parameters, please refer to Table 1 and Table 2.

[0332] Comparative Example 1

[0333] The secondary battery was prepared using a method similar to that in Example 1, except that primary alumina particles (with a volume average particle size Dv50 of approximately 500 nm) were used instead of organosilicon particles in the preparation of the separator. When preparing the coating slurry, alumina, nanocellulose, and acrylic resin were added to deionized water in a specific ratio and mixed thoroughly to obtain the coating slurry.

[0334] Test section

[0335] (1) Thermal shrinkage rate test of the separator film

[0336] Sample preparation: The separation membrane prepared above is punched into samples with a width of 50 mm and a length of 100 mm using a punching machine. Five parallel samples are placed on A4 paper and fixed. Then, the A4 paper containing the samples is placed on corrugated paper with a thickness of 1 mm to 5 mm.

[0337] Sample testing: Place the A4 paper placed on the corrugated paper into a forced-air drying oven. Set the temperature of the forced-air drying oven to 150℃. After the temperature reaches the set temperature and stabilizes for 30 minutes, start timing. After the set time (1 hour in this application), measure the length and width of the release film. The values ​​are marked as a and b, respectively.

[0338] Calculation of heat shrinkage rate: Longitudinal (MD) heat shrinkage rate = [(100-a) / 100]×100%, Transverse (TD) heat shrinkage rate = [(50-b) / 50]×100%, take the average value of 5 parallel samples as the test result.

[0339] (2) Hot box test of secondary batteries

[0340] At 25℃, the secondary batteries were charged at a constant current of 1C to 4.2V, and then charged at a constant voltage until the current was ≤0.05C, and allowed to stand for 5 minutes. Then, each secondary battery was tested in a DHG-9070A DHG series high-temperature oven with fixtures, increasing the temperature from room temperature to 80℃±2℃ at a rate of 5℃ / min and holding for 30 minutes. Afterward, the temperature was increased by 5℃ / min, with each 5℃ increase followed by a 30-minute holding period. The surface temperature of the secondary batteries was monitored during the heating process. The oven temperature at which the temperature began to rise sharply was the oven failure temperature of the secondary battery. A higher oven failure temperature indicates better thermal stability. For accuracy, the average value of five parallel samples was used as the test result.

[0341] (3) Cyclic performance test of secondary batteries

[0342] At 45℃, the secondary battery was charged at a constant current of 1C to 4.2V, and then charged at a constant voltage until the current was ≤0.05C. At this point, the secondary battery was fully charged, and the charging capacity at this point was recorded as the first charge capacity. After the secondary battery was left to stand for 5 minutes, it was discharged at a constant current of 1C to 2.8V. This constituted one charge-discharge cycle, and the discharge capacity at this point was recorded as the first discharge capacity. The secondary battery was subjected to cyclic charge-discharge tests using the above method, and the discharge capacity after each cycle was recorded. The capacity retention rate (%) of the secondary battery after 1000 cycles at 45℃ = discharge capacity after 1000 cycles / discharge capacity of the first cycle × 100%. For accuracy, the average value of 5 parallel samples was taken as the test result.

[0343] Table 1

[0344]

[0345]

[0346] Table 2

[0347]

[0348]

[0349] As can be seen from Tables 1 and 2, by setting a coating including a three-dimensional skeleton structure and organosilicon particles on the surface of the porous substrate of the separator, and by filling at least a portion of the organosilicon particles into the three-dimensional skeleton structure, the separator can have high heat resistance, enabling the secondary battery to achieve high energy density, high thermal stability and long cycle life.

[0350] Tables 1 and 2 also show that by further adjusting the parameters of nanocellulose and organosilicon particles, and satisfying... and This can better improve the performance of the separator and the secondary battery. Based on this, further adjustments can be made... The range of one or more of D1, d1, and L1 can further improve the overall performance of the separator and the secondary battery.

[0351] As can be seen from Tables 1 and 2, the overall performance of the separator and the secondary battery can be further improved by adjusting the mass content of nanocellulose and organosilicon particles.

[0352] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A separating membrane comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein, The coating comprises a three-dimensional framework structure and silicone particles, wherein at least a portion of the silicone particles fills the three-dimensional framework structure. The volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, with units of nm. The average diameter of the material constituting the three-dimensional skeleton structure is denoted as D1, with units of nm. The average length of the material constituting the three-dimensional skeleton structure is denoted as L1, and the unit is nm. Then 0 < D1 / (d1 / ) ≤ 1 and 0 < d1 / (L1 / ) ≤ 1.

2. The separator according to claim 1, wherein, 0.04 ≤ D1 / (d1 / ≤0.85; and / or, 0.04 ≤ d1 / (L1 / ) ≤0.9。 3. The separator according to claim 2, wherein, 0.05 ≤ D1 / (d1 / ≤0.65; and / or, 0.08 ≤ d1 / (L1 / ) ≤0.8。 4. The separator according to claim 1, wherein, The volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, where d1 is less than or equal to 2000 nm; and / or, The average diameter of the material constituting the three-dimensional skeleton structure is denoted as D1, where D1 is less than or equal to 50 nm; and / or, The average length of the material constituting the three-dimensional skeleton structure is denoted as L1, where L1 is 100-3500 nm.

5. The separator according to claim 4, wherein, The volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, where d1 is 275-1500 nm; and / or, The average diameter of the material constituting the three-dimensional framework structure is denoted as D1, where D1 is 10-42 nm; and / or, The average length of the material constituting the three-dimensional skeleton structure is denoted as L1, where L1 is 400-3000 nm.

6. The separator according to any one of claims 1-5, wherein, The organosilicon particles satisfy at least one of the following conditions (1) to (6): (1) The morphology of the organosilicon particles includes spherical and / or near-spherical shapes; (2) The volume distribution particle size Dv90 of the organosilicon particles is less than or equal to 3500 nm; (3) The specific surface area of ​​the organosilicon particles is denoted as S, and its unit is m. 2 / g, 5.0m 2 / g≤S≤12.0m 2 / g; (4) The true density of the organosilicon particles is 1.0-2.0 g / cm³. 3 ; (5) The compacted density of the organosilicon particles at 30000N is 0.3-1.5 g / cm³. 3 ; (6) The number average molecular weight of the organosilicon particles is 20,000 to 80,000.

7. The separator according to claim 6, wherein, The organosilicon particles satisfy at least one of the following conditions (1) to (5): (1) The volume distribution particle size Dv90 of the organosilicon particles is 800-2500 nm; (2) The specific surface area of ​​the organosilicon particles is denoted as S, and its unit is m. 2 / g, 6.0m 2 / g≤S≤10.0m 2 / g; (3) The true density of the organosilicon particles is 1.2-1.7 g / cm³. 3 ; (4) The compacted density of the organosilicon particles at 30000N is 0.5-1.0 g / cm³. 3 ; (5) The number average molecular weight of the organosilicon particles is 30,000 to 50,000.

8. The separator according to any one of claims 1-5, wherein, The content of the organosilicon particles is greater than or equal to 50 wt%, based on the total weight of the coating; and / or, The content of the three-dimensional skeleton structure is less than 50 wt%, based on the total weight of the coating.

9. The separator according to claim 8, wherein, The content of the organosilicon particles is 50-90 wt%, based on the total weight of the coating; and / or, The content of the three-dimensional skeleton structure is 8-48 wt%, based on the total weight of the coating.

10. The separator according to any one of claims 1-5, wherein, The organosilicon particles include a first structural unit; The first structural unit is shown in equation (I): Equation (I); In equation (I), R 20 To R 27 Each independently comprises one or more of substituted or unsubstituted C1-C10 alkyl groups, structural units as shown in formula (I-1), R 20 To R 27 At least one of them includes the structural unit shown in equation (I-1), Equation (I-1); In equation (I-1), R 28 Includes one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; R 29 Includes substituted or unsubstituted C1-C10 alkyl groups.

11. The separator according to claim 10, wherein, R 28 Includes hydrogen atoms, or substituted or unsubstituted C1-C3 alkyl groups.

12. The separator according to claim 10, wherein, R 29 Including substituted or unsubstituted C3-C10 alkyl groups.

13. The separator according to claim 10, wherein, The organosilicon particles further include a second structural unit and / or a third structural unit; The second structural unit has the structure shown in equation (II): Formula (II); In formula (II), R1 includes one or more of hydrogen atoms, substituted or unsubstituted C1-C5 alkyl groups; R2 includes one or more of substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, and substituted or unsubstituted C1-C20 hydroxyalkyl; The third structural unit is represented by formula (III): Formula (III); In formula (III), R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group.

14. The separator according to claim 13, wherein, R1 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.

15. The separator membrane according to claim 13, wherein, R2 includes one or more of a C1-C12 alkyl group, a C3-C12 cycloalkyl group, and a C1-C12 hydroxyalkyl group.

16. The separator according to claim 13, wherein, R3 includes one or more of a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group.

17. The separator according to claim 13, wherein Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is denoted as A%, and 0<A≤20; and / or Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the second structural unit is denoted as B%, and 60≤B<100; and / or Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the third structural unit is denoted as C%, and 0<C≤20.

18. The separator according to claim 17, wherein 5≤A≤20; and / or 60≤B≤80; and / or 5≤C≤20。 19. The separator according to claim 13, wherein, Based on the total molar amount of the first structural unit, the second structural unit and the third structural unit, the molar content of the first structural unit is denoted as A%, the molar content of the second structural unit is denoted as B%, and the molar content of the third structural unit is denoted as C%, the organosilicon particles satisfy at least one of the following conditions (1) to (3): (1) 3≤B / C≤16; (2) 3≤B / A≤16; (3) B:C:A is (12 to 16):(1 to 4):(1 to 4).

20. The separator according to any one of claims 1-5, wherein, The organosilicon particles include a structural unit represented by formula (a): Equation (a); In equation (a), R 14 and R 15 Each is independently selected from hydrogen atoms, substituted or unsubstituted C1-C10 alkyl, hydroxyl or amino atoms.

21. The separator according to claim 20, wherein, R 14 and R 15 Each is independently selected from hydrogen atoms, substituted or unsubstituted C1-C6 alkyl, hydroxyl or amino atoms.

22. The separator according to claim 20, wherein, The organosilicon particles include one or more of polymethylsiloxane, polydimethylsiloxane, polydiethylsiloxane, polymethylhydroxysiloxane, polymethylaminosiloxane, and respective derivatives thereof.

23. The separator according to any one of claims 1-5, wherein, The material constituting the three-dimensional framework structure includes at least one of a linear object, a rod-shaped object, a tubular object, and a stem-shaped object.

24. The separator according to any one of claims 1-5, wherein, The aspect ratio of the material constituting the three-dimensional framework structure is 5 to 150.

25. The separator according to claim 24, wherein, The aspect ratio of the material constituting the three-dimensional framework structure is 20 to 100.

26. The separator according to any one of claims 1-5, wherein, The material constituting the three-dimensional framework structure includes at least one of an organic material and an inorganic material.

27. The separator according to claim 26, wherein, The organic material includes at least one of nanocellulose, polytetrafluoroethylene nanofibers, and polyamide nanofibers.

28. The separator according to claim 27, wherein, The nanocellulose includes at least one of cellulose nanofibers, cellulose nanowhiskers, and bacterial nanocellulose.

29. The separator according to claim 26, wherein, The inorganic material includes at least one of halloysite nanotubes, nanorod-shaped alumina, nanorod-shaped boehmite, nanorod-shaped silica, and glass fibers.

30. The separator according to any one of claims 1-5, wherein, The material constituting the three-dimensional framework structure includes nanocellulose, and the nanocellulose includes at least one of unmodified nanocellulose and modified nanocellulose.

31. The separator membrane according to claim 30, wherein, The modified nanocellulose includes a modifying group, which includes at least one of an amino group, a carboxyl group, an aldehyde group, a sulfonic acid group, a boric acid group, and a phosphate group.

32. The separator according to claim 31, wherein, The modified groups include at least one of sulfonic acid groups, boric acid groups, and phosphate groups.

33. The separator according to claim 31, wherein, The modified nanocellulose includes hydroxyl groups and modified groups, and the molar ratio of the modified groups to the hydroxyl groups is 1:4 to 4:

1.

34. The separator according to claim 33, wherein, The molar ratio of the modified group to the hydroxyl group is 2:3 to 7:

3.

35. The separator according to any one of claims 1-5, wherein, The materials constituting the three-dimensional skeleton structure include sulfonic acid groups, and the sulfur content in the materials constituting the three-dimensional skeleton structure is ≥0.1wt%, based on the total weight of the materials constituting the three-dimensional skeleton structure.

36. The separator according to claim 35, wherein, The materials constituting the three-dimensional skeleton structure include sulfonic acid groups, and the sulfur content in the materials constituting the three-dimensional skeleton structure is 0.2-0.5 wt%, based on the total weight of the materials constituting the three-dimensional skeleton structure.

37. The separator according to any one of claims 1-5, wherein, The coating also includes a non-particulate binder.

38. The separator membrane according to claim 37, wherein, The content of the non-particulate binder in the coating is ≤5 wt%, based on the total weight of the coating.

39. The separator according to claim 37, wherein, The non-particulate binder includes at least one of polyacrylonitrile, acrylic resins, acrylate resins, polyvinyl alcohol, isobutylene-maleic anhydride copolymer, polyacrylamide, sodium carboxymethyl cellulose, carboxymethyl chitosan, sodium alginate, and their respective derivatives.

40. The separator according to any one of claims 1-5, wherein, The thickness of the porous substrate is ≤6μm; and / or, The thickness of the coating is ≤4μm.

41. The separator according to claim 40, wherein, The thickness of the porous substrate is 3-5 μm; and / or, The coating has a thickness of 0.4-3 μm.

42. The separator according to any one of claims 1-5, wherein, The isolation membrane satisfies at least one of the following conditions (1) to (8): (1) The longitudinal thermal shrinkage rate of the isolation membrane at 150℃ for 1 hour is ≤4.5%; (2) The transverse thermal shrinkage rate of the isolation membrane at 150℃ for 1 hour is ≤4.5%; (3) The longitudinal tensile strength of the separator is ≥1600 kg / cm². 2 ; (4) The transverse tensile strength of the separator is ≥1600 kg / cm². 2 ; (5) The wetting length of the isolation membrane is ≥20mm; (6) The wetting rate of the isolation membrane is ≥2 mm / s; (7) The air permeability of the isolation membrane is ≤350s / 100mL; (8) The ion conductivity of the isolation membrane is ≥0.5mS / cm.

43. The separator according to claim 42, wherein, The isolation membrane satisfies at least one of the following conditions (1) to (8): (1) The longitudinal thermal shrinkage rate of the isolation membrane at 150℃ for 1 hour is 0.8%-3%; (2) The transverse thermal shrinkage rate of the isolation membrane at 150℃ for 1 hour is 1%-3%; (3) The longitudinal tensile strength of the separator is 1800-4500 kg / cm. 2 ; (4) The transverse tensile strength of the separator is 1800-4500 kg / cm². 2 ; (5) The wetting length of the isolation membrane is 30-80 mm; (6) The wetting speed of the isolation membrane is 3-10 mm / s; (7) The air permeability of the isolation membrane is 100-270s / 100mL; (8) The ion conductivity of the isolation membrane is 0.55-0.98 mS / cm.

44. A method for preparing the separator membrane according to any one of claims 1-43, comprising the following steps: Provide porous substrates; After kneading silicone particles with a binder, materials for forming a three-dimensional framework structure and a solvent are added and mixed evenly to prepare a coating slurry. The coating slurry is then applied to at least one surface of the porous substrate and dried to obtain a release film. The release film comprises a porous substrate and a coating disposed on at least one surface of the porous substrate. The coating comprises a three-dimensional framework structure and silicone particles, with at least a portion of the silicone particles filling the three-dimensional framework structure. The volume distribution particle size Dv50 of the organosilicon particles is denoted as d1, with units of nm. The average diameter of the material constituting the three-dimensional skeleton structure is denoted as D1, with units of nm. The average length of the material constituting the three-dimensional skeleton structure is denoted as L1, and the unit is nm. Then 0 < D1 / (d1 / ) ≤ 1 and 0 < d1 / (L1 / ) ≤ 1.

45. A secondary battery comprising the separator as described in any one of claims 1-43 or the separator prepared by the method of claim 44.

46. ​​An electrical device comprising the secondary battery of claim 45.

Citation Information

Patent Citations

  • Binder for lithium ion batteries and electrode and separator using same

    CN111164807A

  • Three-dimensional porous silicon / carbon composite material, method for preparing same, and use thereof

    US20220310989A1